The Criticality of Connecting People to Financial Results - an ROI Calculation Model for Romanian FSOs - Daniela Niculescu (Amfiteatru Economic Journal, 2016)
Organisational culture and employee engagement have been the focus of recent broad-based research efforts. Adding this concern to the revealed importance of performance indicators on human capital, and that their use is getting momentum, in order to attach financial values to knowledge management assets, it becomes more and more critical to measure human capital value. Key for Romanian FSO's managers becomes to consider that both human and financial values have a focus on adding value in every process and function in the organisation, and to perpetuate organisational profitability by the corporate culture, on the one hand, where culture is a powerful factor that helps a company to engage, on the other hand, talented people. There is a substantial concern on using ROI on Learning and Development programmes, but whilst this is still declared, Romanian FSOs do not yet have a consistent method to measure it. This study is showing the criticality of connecting people to financial results and data analysis suggests that ROI calculation has a positive impact on creating and fostering a powerful organisational culture and that employees' awareness of ROI values within their organisation has a powerful effect on their sense of engagement. Our findings have a more practical implication for the analysed industry by shaping a formal ROI measurement mechanisms blueprint, an ROI calculation model for the Romanian FSOs, in the form of a mechanism that could be employed when considering the design of an ROI Methodology for Romanian FSOs.
Keywords: O15; M15; D83; O21; 330; ROI on learning and development programmes; human capital; organisational culture; employee engagement; knowledge management